Higher serum sclerostin levels and insufficiency of vitamin D are strongly associated with vertebral fractures in hemodialysis patients: a case control study. Issue 2 (February 2017) - Atteritano, M.; Di Mauro, E.; Canale, V.; Bruzzese, A.; Ricciardi, C.; Cernaro, V.; Lacquaniti, A.; Buemi, M.; Santoro, D.
Abstract Summary In hemodialysis patients, vertebral fractures were associated with elevated sclerostin levels, suggesting that sclerostin could reflect bone fragility in these patients. Introduction Fragility fractures are common in hemodialysis patients. The aims of our study were to determine the prevalence of vertebral fracture and analyze associations between sclerostin serum levels and vertebral fractures in hemodialysis patients. Methods Ninety-two hemodialysis patients and 100 controls matched for age and sex were studied. Bone mineral density was measured by ultrasonography at non-dominant heel. The markers of bone turnover included serum osteocalcin, C-terminal telopeptide, and sclerostin. All participants underwent radiography of the thoracic and lumbar spine to ascertain the presence of vertebral fractures. Results Bone ultrasound parameters at calcaneus were significantly lower in hemodialysis patients compared with controls; bone turnover markers and parathyroid hormone level were significantly higher, while serum of 25-OH-D3 was significantly lower in hemodialysis group. One or more moderate or severe vertebral fractures were found in 38 hemodialysis patients, whereas in control group, 10 patients had a vertebral fracture. In hemodialysis group, the comparison between patients with and without vertebral fractures showed that the patients with vertebral fractures had the serum sclerostin levels statistically higher than patients without vertebral, while serum levels of 25-OH-D3 was significantly lower in patients with vertebral fractures compared to the patients without vertebral fractures. Multivariate analysis disclosed that sclerostin levels were associated with an increased risk of vertebral fractures in hemodialysis patients after adjusting for multiple variables. Conclusions Our data shows high prevalence of vertebral fractures in hemodialysis patients and that it is associated with elevated sclerostin levels, reflecting bone fragility in these patients.